Optimalisai Kesehatan Ibu Hamil Beresiko Tinggi dan Upaya Preventif terhadap Kejadian Stunting di Desa Jlegongan - Fauzan, Muhammad; Jannah, Arrinda Miftachul; Wahyuningsih, Alifia Arienda; Zuhdi, Hilal; Rahman, Muhammad Fadhila; Prayoga, Aqbil Fajar; Az Zahra, Taqiyyatuts Tsabitah; Adzqiya, Fatan; Pribadi, Fachsheila H.; Nurwulandari, Vionita; Dhiya An, Alfun (Universitas Muhammadiyah Yogyakarta, 2025)
The incidence of stunting is caused by various things, including maternal factors during pregnancy, nutritional intake during toddlerhood, infection, environmental factors and parenting. Prevention can be done early, namely when the baby is in the womb (when the mother is pregnant) must get balanced nutrition. In the Jlegongan Padukuhan area, there are several pregnant women experiencing high-risk pregnancies. In addition, pregnant women in the Jlegongan Padukuhan area are less familiar with the nutritional needs of pregnant women, as well as the consequences that occur if nutritional needs during pregnancy are not met properly. The purpose of this community service project is to increase the knowledge and regeneration of posyandu cadres about the importance of proper nutrition during pregnancy as an early effort to prevent stunting. The Real Work Lecture activity method uses a participatory approach with a qualitative descriptive technique that aims to understand the conditions and health problems of pregnant women in depth consisting of observation, planning, practice and counseling. The activities carried out are Counseling on Stunting Prevention, DASHAT (Healthy Kitchen to Overcome Stunting), Counseling on Reproductive Health, Family Planning, and Productive Age Women, and Anthropometric Measurements for Toddlers. The results of the Nyara Work Lecture obtained an increase in good knowledge about stunting and the importance of nutrition during pregnancy by 90% compared to the knowledge before the majority of activities carried out by 50%. Activities are expected to be carried out and evaluated regularly as an effort to prevent stunting.